Особливості використання елементів культури рідного краю у соціалізації дітей передшкільного віку - Гришко, Ярослава Вікторівна (My University, 2022)
У науковій роботі проаналізовано специфіку соціалізації дітей передшкільного віку засобами культури рідного краю. Розглянуто соціалізуючий потенціал означеної культури, визначено її складові. Розкрито специфіку передшкільного віку щодо можливості дитини пізнавати рідний край, його природу, соціум, історико-культурну спадщину. З метою проведення констатувального етапу експериментального дослідження розроблено необхідний діагностичний інструментарій. Виявлено рівні соціалізованості дітей передшкільного віку засобами культури рідного краю. Проаналізовано чинники впливу на ефективність процесу соціалізації дошкільників 5-6 років з урахуванням культури рідного краю. На основі отриманих експериментальних даних розроблено педагогічні умови соціалізації дітей передшкільного віку засобами елементів культури рідного краю. Укладено методичні матеріали до кожної з означених умов, що повинно, на думку автора, підвищити ефективність роботи вихователя ЗДО стосовно соціалізації дітей передшкільного віку з опорою на історико-культурну спадщину рідного краю.
The scientific work analyzes the specifics of socialization of pre-school children by means of culture of their native land. The socializing potential of this culture is considered, and its components are determined. The article reveals the specifics of pre-school age regarding the child's ability to learn about their native land, its nature, society, historical and cultural heritage. In order to conduct the ascertaining stage of the experimental study, the necessary diagnostic tools have been developed. The levels of socialization of pre-school children by means of culture of their native land are revealed. The factors influencing the effectiveness of the socialization process of preschool children aged 5-6 years are analyzed, taking into account the culture of their native land. Based on the obtained experimental data, pedagogical conditions for socialization of pre-school children by means of elements of the culture of their native land are developed. Methodological materials for each of these conditions are compiled, which, in the author's opinion, should increase the effectiveness of the work of a zdo teacher on socialization of pre-school children based on the historical and cultural heritage of their native land. Keywords: socialization, culture of the native land, regional culture, socio-civil competence, pre-school age.
Keywords: соціалізація; культура рідного краю; регіональна культура; соціально-громадянська компетентність; діти передшкільного віку